Impact of resistive MHD plasma response on perturbation field sidebands. (3rd June 2016) - Orlov, D M; Evans, T E; Moyer, R A; Lyons, B C; Ferraro, N M; Park, G-Y
Abstract: Single fluid linear simulations of a KSTAR RMP ELM suppressed discharge with the M3D-C 1 resistive magnetohydrodynamic code have been performed for the first time. The simulations show that the application of the n = 1 perturbation using the KSTAR in-vessel control coils (IVCC), which apply modest levels of n = 3 sidebands ( 20% of the n = 1), leads to levels of n = 3 sideband that are comparable to the n = 1 when plasma response is included. This is due to the reduced level of screening of the rational-surface-resonant n = 3 component relative to the rational-surface-resonant n = 1 component. The n = 3 sidebands could play a similar role in ELM suppression on KSTAR as the toroidal sidebands ( n = 1, 2, 4) in DIII-D n = 3 ELM suppression with missing I-coil segments (Paz Soldan et al 2014 Nucl. Fusion 54 073013). This result may help to explain the uniqueness of ELM suppression with n = 1 perturbations in KSTAR since the effective perturbation is a mixed n = 1/ n = 3 perturbation similar to n = 3 ELM suppression in DIII-D.